Predictors of Atrial Fibrillation Recurrence in Hyperthyroid and Euthyroid Patients - Gürdoğan,Muhammet (2016)
Background: Atrial fibrillation (AF) is the most common arrhythmia in adults, and is encountered in 10-15% of the patients with hyperthyroidism. Unless euthyroidism is restored, pharmacological or electrical cardioversion is controversial in patients with AF who remain hyperthyroid. Objective: The aim of this study was to assess the efficacy of electrical cardioversion and predictors of AF recurrence in hyperthyroid and euthyroid patients. Methods: The study included 33 hyperthyroid (21 males) and 48 euthyroid (17 males) patients with persistent AF. The patients were sedated with intravenous midazolam before undergoing electrical cardioversion delivered by synchronized biphasic shocks. Rates of AF recurrence were recorded. Results: Mean follow-up was 23.63 ± 3.74 months in the hyperthyroid group and 22.78 ± 3.15 months in the euthyroid group (p = 0.51). AF recurred in 14 (43.8%) and 21 (44.7%) patients in each group, respectively (p = 0.93). Multivariate regression analysis in each group showed that AF duration was the only predictor of AF recurrence, with odds ratios of 1.38 (95% confidence interval [CI] = 1.05 - 1.82, p = 0.02) in the hyperthyroid group and 1.42 (95% CI = 1.05 - 1.91, p= 0.02) in the euthyroid group. Conclusion: Rates of long-term AF recurrence were similar in successfully cardioverted hyperthyroid and euthyroid patients. The only predictor of AF recurrence in both groups was AF duration.